Synthesis, Characterization And Mesomorphic Properties Of Symmetric And Non-Symmetric Isoflavone Oligomers - Chan, Tze Nee (2012)
Four new series of symmetric and non-symmetric isoflavone-based liquid crystal oligomers have been synthesized and characterized. These oligomers comprised of three series of non-symmetric dimers, namely 7-[{4-[4'-((S)-2''-methylbutyloxy)carbonylphenyl]phenoxy}alkyloxy]-3-(4'-decyloxyphenyl)-4H-1-benzopyran-4-ones (BP-n-I), 7-[{4-[4'-((S)-2''-methylbutyloxy)carbonyl phenyl]phenoxy}decyloxy]-3-(4'-substitutedphenyl)-4H-1-benzopyran-4-ones (BPI-R) and 7-[{4-[(4'-methoxyphenyl)diazenyl]phenoxy}alkyloxy]-3-(4'-methoxy phenyl)-4H-1-benzopyran-4-ones (AB-n-I), and a series of symmetric trimers: 1,3-bis{[3-(4'-decyloxyphenyl)-4H-1-benzopyran-4-one-7-oxy]alkyloxy}benzenes (BI-n-B). All oligomeric mesogens differ from one another in term of mesogenic moieties and spacer length.